Nonhematological mechanisms of improved sea-level performance after hypoxic exposure - Gore, C. J.; Clark, S. A.; Saunders, P. U. (Medicine & Science in Sports & Exercise, 2007)
Altitude training has been used regularly for the past five decades by elite endurance athletes, with the goal of improving performance at sea level. The dominant paradigm is that the improved performance at sea level is due primarily to an accelerated erythropoietic response due to the reduced oxygen available at altitude, leading to an increase in red cell mass, maximal oxygen uptake, and competitive performance. Blood doping and exogenous use of erythropoietin demonstrate the unequivocal performance benefits of more red blood cells to an athlete, but it is perhaps revealing that long-term residence at high altitude does not increase hemoglobin concentration in Tibetans and Ethiopians compared with the polycythemia commonly observed in Andeans. This review also explores evidence of factors other than accelerated erythropoiesis that can contribute to improved athletic performance at sea level after living and/or training in natural or artificial hypoxia. We describe a range of studies that have demonstrated performance improvements after various forms of altitude exposures despite no increase in red cell mass. In addition, the multifactor cascade of responses induced by hypoxia includes angiogenesis, glucose transport, glycolysis, and pH regulation, each of which may partially explain improved endurance performance independent of a larger number of red blood cells. Specific beneficial nonhematological factors include improved muscle efficiency probably at a mitochondrial level, greater muscle buffering, and the ability to tolerate lactic acid production. Future research should examine both hematological and nonhematological mechanisms of adaptation to hypoxia that might enhance the performance of elite athletes at sea level.